The Role of Financial Literacy, Financial Inclusion, and Financial Management in Supporting the Sustainability of MSMEs Using QRIS in Kemiling Permai, Bandar Lampung - Ayu Rista; Erna Listyaningsih; Hiro Sejati (International Journal of Management, Economic and Accounting, 2026)
This study aims to empirically analyze the individual and simultaneous effects of financial literacy, financial inclusion, and financial management on the sustainability of Micro, Small, and Medium Enterprises (MSMEs) using QRIS in Kemiling Permai, Bandar Lampung. This study employs a quantitative methodology with an explanatory research design. The sampling technique utilized was purposive sampling, resulting in a sample of 95 MSME respondents. Data was collected through a 5-point Likert scale questionnaire and analyzed using multiple linear regression. The partial test results indicate that financial literacy does not have a positive and significant effect on MSME sustainability. Conversely, financial inclusion and financial management have a positive and significant effect on MSME sustainability. Simultaneously, financial literacy, financial inclusion, and financial management have a significant effect on the sustainability of MSMEs using QRIS, collectively explaining 30.6% of the variance. The study concludes that MSME sustainability is driven more by the practical ability of business actors to access digital financial services and manage finances effectively than by theoretical financial knowledge alone.